Situaciones didácticas de Brousseau en el mejoramiento de las competencias en el área de matemáticas de estudiantes del primer nivel de la Facultad de Ciencias de la Educación y Humanidades UNAP Iquitos 2021 - Gomez Casimiro, Henry Jeison (2025)
The present study aimed to evaluate the effect of applying Brousseau's didactic situations on improving mathematics competencies among first-level students of the Faculty of Education and Humanities - UNAP, Iquitos 2021. The methodology used was a field and quasi-experimental design. Data collection was based on two techniques: a performance test and a rubric. The sample consisted of students enrolled in the Mathematics II course, divided into an experimental group with 30 students and a control group with 30 students, for a total of 60 students. The results indicate that the application of Brousseau's didactic situations significantly improves competencies in mathematics, as evidenced by a comparison between the initial and final situations, which showed statistically significant changes (p < 0.05). It is concluded that the application of Brousseau's didactic situations significantly enhances the resolution of problems related to regularity, equivalence, and change, thereby improving students' competencies in mathematics.